Insight Into the Relation Between Nutritional Benefits of Aquaculture Products and its Consumption Hazards: A Global Viewpoint - Arshad, Naufal; Samat, Narimah; Lee, Lai Kuan (Frontiers in Marine Science, 2022)
Aquaculture plays a huge role in supporting the needs and demands of fish and other aquatic organisms globally. Being a vital contributor in the fisheries sector, aquatic sources derived from the aquaculture industry are well-known for their high nutritive values that are compromised with high-quality protein, essential omega-3 fatty acids, vitamins, and minerals. Aquaculture has also widened fish availability to regions and countries with limited access to farmed species, leading to improved nutrition and food security. However, the presence of dangerous contaminants, notably heavy metals, endocrine disrupting compounds, polycyclic aromatic hydrocarbons, microplastics, as well as antimicrobial drug residues, has been detected in the aquaculture products. In conjunction, the risk–benefit assessment (RBA) approach has been proposed to be used as a meaningful tool for evaluating the health impacts of the consumption of aquatic sources on the targeted population. This narrative review outlines a compilation of aquaculture products as a nutritional source for human consumption. The aquaculture industry is well-appreciated, especially in low-income countries, for achieving sustainable food security. The organoleptics and preferences of aquaculture products as means of dietary variations were demonstrated. The damaging contaminants contained in the commercially available aquaculture products were quantitatively outlined. Furthermore, the adaptation of the risk–benefit approach underlying its potent impacts on public health concerns, with its current challenges and limitations, is elucidated.